Ensaios sobre inflação: uma análise a partir de grupos, núcleos e regiões. - Lucena, Raphael Douglas de Freitas (2025)
This thesis seeks to highlight distinct, but complementary, aspects of the inflationary process in Brazil, focusing on group, structural and regional analysis, and its relationship with the dynamics of inflation. The first chapter analyzes the spectrum of inflation groups in Brazil in the period from 2000:01 to 2023:09, to verify the persistence of the inflationary process. The results of the decomposition of the wavelet power spectrum, proposed by Aguiar-Conraria and Soares (2014), indicate that most of the variability of the IPCA is concentrated in cycles of 1 to 4 years. However, from 2016 onwards, inflation began to be dominated by longer fluctuations, with a transition to cycles of 2 to 4 years. The second chapter investigated the existence of a long-term relationship between items excluded from the inflation core calculated by the Central Bank of Brazil (BCB) and the IPCA for the period between 2000.01 and 2023.03. In this approach, wavelet analysis tools (coherence and phase difference) were used. The results indicate a pro-cyclical relationship between the headline and the EXFE core, with the headline driving movements at frequencies between 48 and 96 months. In addition, pro-cyclical movements were found at frequencies between 24 and 96 months, with food and energy inflation driving fluctuations in the headline, which contradicts the hypothesis that, in the long run, the core does not respond to deviations in the headline and its excluded items. The third chapter examines how inflation in metropolitan regions is synchronized and linked to the inflation rate at the national level. For this purpose, a set of continuous wavelet transform (CWT) tools were used on inflation data from 2000.01 to 2024.08. The results indicate that regional inflation is highly synchronized with national inflation in long-term cycles (4 to 8 years), with significant areas above 80%. In the short term, this value is between 30% and 60%, particularly in the North and Northeast regions. As for the direction of these movements, a pro-cyclical relationship was confirmed, but without clear leadership in the long term, with inflation in the Northeast region (Recife and Salvador) driving national movements in specific periods, while in the Southeast (Belo Horizonte), the national cycle has led regional inflation movements. The estimated coefficients indicate that national shocks may impact some regions differently in the short and long term.